SILVER NANOPARTICLES AS ANTIVIRAL-A MINI REVIEW - Abdulazem, Lubna (PT. Antis International Publisher, 2025)
Objective: There are many different species that nanoparticles can suppress, such as bacteria, algae, fungus, archaea, and a vast class of viruses. Method: The method of action involves preventing the creation of the cell membrane or its function, interfering with energy transmission, generating harmful reactive oxygen species (ROS), and preventing or lowering the synthesis of RNA and DNA. Results: Numerous nanomaterials, including those based on silicon, carbon, and metals, as well as nanoarchitectures, have been effectively employed to combat various viruses. The solid-state activity of these nanoarchitecture-based virucidal materials (also known as nano-antivirals) has been firmly supported by recent research. The development of many items, including high-touch surfaces and fabric, benefits greatly from their use. Novelty: The development of scalable and sustainable nano-antiviral products with contact-killing capabilities is recommended in this study, which carefully and critically evaluates current developments in the use of nanomaterials to block the effectiveness of Rotavirus, one of the enteroviruses that kill children.